Biological of Malaysian canes modified with polymer. - Hamid, Norul Hisham; Adlin , Sabrina; Muhammad, Roseley; Halis, Rasmina; Ujang, Salmiah (Forest Research Institute Malaysia, 2006)

(untitled)
The biological resistance against white and brown rot fungi of Calamus manan (manau) and C. ornatus (mantang) canes modified with polymer was investigated.